Planctomycetes as a Vital Constituent of the Microbial Communities Inhabiting Different Layers of the Meromictic Lake Sælenvannet (Norway) - Storesund, Julia E. (Microorganisms, 2020)
Meromictic lakes are permanently stratified lakes that display steep gradients in salinity, oxygen and sulphur compounds tightly linked to bacterial community structure and diversity. Lake Sælenvannet is a meromictic lake located south of Bergen, Norway. The 26 m deep lake is connected to the open sea and permanently stratified into two layers separated by a chemocline. The upper water layer is brackish with major input from water runoff from the surroundings. The bottom layer consists of old saline water with low or no oxygen concentrations. Bacteria from phylum Planctomycetes are reported to be ubiquitous in lake environments. They are involved in the degradation of complex carbon sources in aquatic environments and are also linked to anaerobic processes such as fermentation and sulphur reduction. To study Planctomycete distribution along a chemical gradient, we sampled the water column throughout Lake Sælenvannet in 2012 and profiled the microbial community using 16S rRNA amplicon sequencing (metabarcoding) with 454 pyrosequencing. Planctomycetes related 16S rRNA gene sequences were found to be present both in the oxic and anoxic parts of the lake and showed an uneven distribution throughout the water column, with the highest relative abundance of 10% found in the saline anoxic layer at 15 m depth. In a follow-up study in 2014, samples from eight different depths were collected for enrichment and isolation of novel Planctomycetes. This study resulted in successful isolation in pure culture of 10 isolates affiliated to four different genera from the family Planctomycetaceae. One strain closely related to Blastopirellula cremea was isolated from 9 m depth, and two novel strains affiliated to the genera Stieleria and Gimesia were isolated at 7 and 9 m depths, respectively. Furthermore, seven isolates with identical 16S rRNA gene sequences were retrieved from seven different depths which varied greatly in salinity and chemical composition. These isolates likely represent a new species affiliated to Rubinisphaera. The adaptation of this novel Planctomycete to water depths spanning the entire chemical gradient could indicate a high phenotypic plasticity and/or a very efficient survival strategy. Overall, our results show the presence of a diverse group of Planctomycetes in Lake Sælenvannet, with a strong potential for novel adaptations to chemical stress factors.